2011
DOI: 10.1007/s00426-011-0384-x
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and perceptual-motor performance: toward an integrated model of concepts, mechanisms, and processes

Abstract: Under anxiety, people sometimes perform poorly. This concerns cognitive performance (e.g., taking an important exam) as well as perceptual-motor performance (e.g., picking up a cup from a table). There is still much debate about how anxiety affects perceptual-motor performance. In the current paper we review the experimental literature on anxiety and perceptual-motor performance, thereby focusing on how anxiety affects the perception, selection, and realization of action possibilities. Based on this review we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
195
5
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 198 publications
(216 citation statements)
references
References 87 publications
(222 reference statements)
14
195
5
2
Order By: Relevance
“…These findings are in contradiction with other authors who have reported decreased ART prior to examination [16]. Our findings slightly related to integrated model which is strongly based on distraction model [17]. Study also reported that under stressful conditions, the cognitive system is overloaded thereby it reduces a person's attentional resources [18].…”
Section: Discussioncontrasting
confidence: 57%
“…These findings are in contradiction with other authors who have reported decreased ART prior to examination [16]. Our findings slightly related to integrated model which is strongly based on distraction model [17]. Study also reported that under stressful conditions, the cognitive system is overloaded thereby it reduces a person's attentional resources [18].…”
Section: Discussioncontrasting
confidence: 57%
“…The distraction and self-focus models of choking have been initially viewed as two distinct or competing models (e.g., Beilock & Carr, 2001;Lewis & Linder, 1997). Most recently, however, researchers have begun to suggest that the two choking models are not distinct but may overlap (Gröpel & Beckmann, 2017b;Mesagno, Geukes, et al, 2015;Nieuwenhuys & Oudejans, 2012). For example, Nieuwenhuys and Oudejans argue that self-focus may be viewed as a type of internal distraction.…”
Section: Future Researchmentioning
confidence: 99%
“…In such cases, exploiting already existing levels of automaticity to better establish the skill under anxiety conditions , as opposed to refining technique, might be a more appropriate solution (see Schack & Bar-Eli, 2007). Of course, it is entirely possible that several interrelated factors may act to mediate suboptimal performance (e.g., Nieuwenhuys & Oudejans, 2012), so focusing on the demonstrably important (i.e., causative as opposed to associated) contributor(s) are essential. Furthermore, depending on the presenting circumstances (e.g., time relative to a competitive season, availability of resources), shortterm trade-off decisions that provide immediate relief may be more appropriate, retaining the intention of conducting more extensive work later on.…”
mentioning
confidence: 99%